Cosmetics industry: market trends of biocosmetics - Aponte, Gloria María (2025)
Biocosmetics, products which utilize natural or biologically derived components, are gaining prominence due to their safety, sustainability, and effectiveness. Among their advantages are a lower risk of irritation and allergies, biodegradability, and applications in skincare, makeup, hair care, and perfumes. This study examines global market trends in the production and use of biocosmetics over the past decade, employing content analysis and a literature review of key market reports. The market is projected to reach $8.75 billion by 2032, with a compound annual growth rate (CAGR) estimated between 4.49% and 6.90% for the period 2019–2032. The findings highlight a transformation in the cosmetic industry, with biocosmetics emerging as a rapidly growing sector driven by increasing demand for safe, sustainable, and effective products